Analysis of Cognitive Revised Bloom's Taxonomy in the PAI RPP Document at Sinarmekar Elementary School, Sukabumi Regency - Irmawati; Khozin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Purpose of this research is to determine the bloom taxonomy analysis of cognitive revisions in the PAI RPP document at Sinarmekar Elementary School, Sukabumi Regency. This type of research is descriptive research which aims to describe the cognitive level of RPP PAI at the elementary school level based on the cognitive domain of the Revised Bloom's Taxonomy. RRP cognitive level is measured through descriptions of cognitive abilities. Data collection in this research uses the documentation method, namely a method that searches for data regarding variables in the form of transcript notes, books, newspapers, magazines, inscriptions, minutes, meetings, leggers, agendas, and so on. Bloom's Taxonomy initially classified learning objectives in the cognitive domain into six levels, namely knowledge, comprehension, application, analysis, synthesis, and evaluation.